2021
DOI: 10.1038/s41394-021-00412-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a high-fat/high-carbohydrate meal on leukocyte populations in adults with chronic spinal cord injury

Abstract: Study design Secondary analysis of aggregated case series data. Objectives To examine the effects of a high-fat/high-carbohydrate meal on leukocyte populations in adults with a chronic SCI. Setting University-based laboratories in British Columbia, Canada. Methods Ten individuals (M = 9) with a traumatic SCI (>1-year post-injury; M = 15.5 years; n = 2 sensory complete, n = 7 motor complete) participated in this study. Participants arrived fasted (≥12 h) prior to both the control (quiet sitting, no food/ drink)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A four-day washout period provided between conditions to ensure no carry-over effects ( 23 ). The meal condition data are not a part of the current study as they did not include cognitive function or BDNF analyses and have been reported elsewhere ( 24 ). Participants arrived at the lab between 9:00 and 10:00 am following an overnight fast (≥12 h).…”
Section: Methodsmentioning
confidence: 99%
“…A four-day washout period provided between conditions to ensure no carry-over effects ( 23 ). The meal condition data are not a part of the current study as they did not include cognitive function or BDNF analyses and have been reported elsewhere ( 24 ). Participants arrived at the lab between 9:00 and 10:00 am following an overnight fast (≥12 h).…”
Section: Methodsmentioning
confidence: 99%